Estimation of radiation risks under photonuclear production of 67Cu and 99Mo isotopes - Ayzatskiy, M.I.; Dovbnya, A.N.; Tenishev, A.Eh.; Torgovkin, A.V.; Uvarov, V.L.; Shevchenko, V.A.; Shramenko, B.I.; Ehst, D. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The activated bremsstrahlung converter and isotopic target are the main sources of radiation hazard in the isotope production at electron accelerators. In experiments at the NSC KIPT accelerators KUT-30 and LU-40m, intended to produce 99Mo and 67Cu isotopes in the targets based on natural Mo and Zn, the output devices were exposed to radiation. Induced activities of the tantalum converter, of targets and cooling water were measured. The exposure dose rates provided by each element and the activity decrease after the exposure were determined.